Fracture, Fatigue and Structural Integrity of Metallic Materials - Álvarez Laso, José Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Fracture, fatigue, and other subcritical processes, such as creep crack growth or stress corrosion cracking, present numerous open issues from both scientific and industrial points of view. These phenomena are of special interest in industrial and civil metallic structures, such as pipes, vessels, machinery, aircrafts, ship hulls, and bridges, given that their failure may imply catastrophic consequences for human life, the natural environment, and/or the economy. Moreover, an adequate management of their operational life, defining suitable inspection periods, repairs, or replacements, requires their safety or unsafety conditions to be defined. The analysis of these technological challenges requires accurate comprehensive assessment tools based on solid theoretical foundations as well as structural integrity assessment standards or procedures incorporating such tools into industrial practice.